Real Time Temperature Control Using LabVIEW Based on PID Algorithm and Power Electronics - Haithem Ali Ali; Noura Mohammed Salem; Retaj Mohammed Abdullah; Sumaya Basher Abdullah (African Journal of Advanced Pure and Applied Sciences, 2023)
There are many temperature control systems for either heating or cooling, the most famous of which is the ON-OFF control system. Most of these systems draw a high current when starting, which leads to a large consumption of energy, this affects the overall efficiency of the system, and the response of the system is not completely as required, as an overshoot occurs in response due to continuous operation and stopping. Some systems are not greatly affected by the overshoot rate that occurs in the response of the system, and some systems, if the temperature control is not very accurate, will lead to the failure of the entire system and will entail major problems. An example of this is the incubator, which is a machine that adjusts the appropriate temperature and humidity that the eggs need to hatch. Any change in temperature causes problems and defects and reduces the hatching rate a lot, so this process requires constant monitoring of the temperatures in the incubator. In this project, the focus was on solving two problems: the problem of energy consumption in heating devices and the problem of override in the system response. By designing the feedback control system to maintain the system temperature within a particular range based on a feedback signal from the temperature sensor, as a result, the power consumption will be reduced, the overshoot will be eliminated, and the system response will be obtained. LabVIEW program was used to draw the system response. The parameters of the controller were modified using trial and error method to obtain good system characteristics. System results show that the controller was able to adjust the temperature without an overshoot.